ANALISIS PRESEPSI PENGGUNAAN APLIKASI DIGITAL BANKING OLEH MAHASISWA FEBI UNTUK PEMBAYARAN UKT DI UIN GUSDUR - Putri, Fariska Amalia; Syamsuddin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This research tries to find out how UKT (Single Tuition Fee) payments at UIN Gusdur Pekalongan are perceived by students majoring in Islamic banking FEBI (Faculty of Economics and Islamic Business). Primary data used in this study was collected through interviews with respondents using descriptive qualitative methods. A technical tool called